Effects of Meteor-Impacts on Stationary Satellites - K. Purbosiswojo (Journal of Mathematical and Fundamental Sciences, 1964)
Abstract. In this paper the changes of the orbital elements of stationary satellites due to meteor-impacts are discussed. From these changes in principle one should be able to draw the conclusion whether or not there exist a correlation between meteor-mass and velocity.It has been shown here, how to detect and estimate an increase in space-density and the velocity-vector of any meteor stream T  which the satellite traverses. Numerical results, however, show that effects of meteor-impacts  can be neglected at all.Ichtisar. Dalam tulisan ini diperbintjangkan, pengaruh pertumbuknja meteor2 pada satelit stasioner. Pada prinsipnja orang dapat mengetahui ada tidaknja korelasi antara massa dan ketjepatan meteor dari perubahan2 orbit satelit tersebut. Djuga ditundjukkan bahwa pada prinspinja orang dapat mendjabarkan dari perubahan2 jang tersebut kepadatan ruang dan vektor ketjepatan suatu aliran meteor jang dilintasi satelit. Tetapi hasil2 numerik membuktikan bahwa pengaruh meteor dapat diabaikan sama sekali.